2022
DOI: 10.1186/s13034-022-00521-7
|View full text |Cite
|
Sign up to set email alerts
|

Examining how and why polygenic dopamine composite levels moderate adolescents’ vulnerability to peer victimization

Abstract: Extensive literature documents that dopaminergic genes play an important role in the link between adverse environments and adolescents’ problem behavior. However, little is known about the potential mechanism underlying adolescents’ vulnerability to peer victimization. The current study examined the effect of the interplay between a polygenic dopamine composite (i.e., COMT Val158Met and DRD2-141C Ins/Del polymorphisms) and peer victimization on adolescents’ externalizing problems as well as the mediating role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…Other work, using a polygenic dopamine composite score, demonstrated that dopaminergic genes moderated adolescent vulnerability to adverse social factors (e.g., peer victimization), via emotional dysregulation (in girls but not boys). Specifically, compared with individuals with composite scores indicative of greater dopamine activity, adolescents with lower dopamine activity reported higher levels of emotional dysregulation when facing victimization and, in turn, displayed more externalizing (Gao et al., 2022). Together, these studies suggest that dopaminergic differences may be salient factors in determining individual sensitivity and responsiveness to environmental circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Other work, using a polygenic dopamine composite score, demonstrated that dopaminergic genes moderated adolescent vulnerability to adverse social factors (e.g., peer victimization), via emotional dysregulation (in girls but not boys). Specifically, compared with individuals with composite scores indicative of greater dopamine activity, adolescents with lower dopamine activity reported higher levels of emotional dysregulation when facing victimization and, in turn, displayed more externalizing (Gao et al., 2022). Together, these studies suggest that dopaminergic differences may be salient factors in determining individual sensitivity and responsiveness to environmental circumstances.…”
Section: Discussionmentioning
confidence: 99%